Change in Objectively Measured Activity Levels Resulting from the EMPOWER Study Lifestyle Intervention. Issue 1 (2022) - Rockette-Wagner, Bonny; Cheng, Jessica; Bizhanova, Zhadyra; Kriska, Andrea; Sereika, Susan; Kline, Chris; Imes, Chris; Kariuki, Jacob; Mendez, Dara; Burke, Lora
Abstract : ABSTRACT: This study aimed to examine changes in physical activity (PA) during a behavioral weight loss intervention and to determine baseline factors associated with PA goal achievement. Overweight/obese community-dwelling adults with valid PA accelerometer data ( n = 116; mean age, 51.7 yr; 89% female; 83% non-Hispanic White) were recruited into a single-arm prospective cohort study examining the effects of a 12-month intervention that included 24 in-person group sessions, weight loss, calorie, fat gram, and PA goals, self-monitoring, and feedback. Minutes of moderate to vigorous PA (MVPA) and steps were measured using a waist-worn accelerometer (ActiGraph GT3x) at baseline, 6 months, and 12 months. Achievement of the 150-min·wk −1 MVPA goal was examined using total minutes and bout minutes (i.e., counting only PA occurring in bouts ≥10 min in length). Change in PA was analyzed using nonparametric tests for multiple comparisons. Associations of factors with meeting the PA goal were modeled using binary logistic regression. At 6 months, there were increases from baseline in MVPA (median [p25, p75] = 5.3 [−0.9, 17.6] min·d −1 ) and steps (863 [−145, 2790] steps per day), both P < 0.001. At 12 months, improvements were attenuated (MVPA = 2.4 [−2.0, 11.4] min·d −1, P = 0.047; steps = 374 [−570, 1804], P = 0.14). At 6 months, 33.6% of individuals met the PA goal (using total or bout minutes). At 12 months, the percent meeting the goal using total MVPA (31%) differed from bout MVPA (22.4%). Male gender (odds ratios = 4.14, P = 0.027) and an autumn program start (vs winter; odds ratios = 3.39, P = 0.011) were associated with greater odds of goal achievement at 6 months. The intervention increased PA goal achievement at 6 and 12 months with many making clinically meaningful improvements. Our results suggest that female participants may require extra support toward improving PA levels. Abstract : Supplemental digital content is available in the text.